A Dimetalloxycarbene Bonding Mode and Reductive Coupling Mechanism for Oxalate Formation from CO21. Issue 31 (25th June 2015) - Paparo, Albert; Silvia, Jared S.; Kefalidis, Christos E.; Spaniol, Thomas P.; Maron, Laurent; Okuda, Jun; Cummins, Christopher C.
Abstract We describe the stable and isolable dimetalloxycarbene [(TiX3)2(μ2‐CO2‐κ2C, O:κO′)] 5, where X=N‐(tert‐butyl)‐3, 5‐dimethylanilide, which is stabilized by fluctuating μ2‐κ2C, O:κ1O′ coordination of the carbene carbon to both titanium centers of the dinuclear complex 5, as shown by variable‐temperature NMR studies. Quantum chemical calculations on the unmodified molecule indicated a higher energy of only +10.5 kJ mol−1 for the μ2‐κ1O:κ1O′ bonding mode of the free dimetalloxycarbene compared to the μ2‐κ2C, O:κ1O′ bonding mode of the masked dimetalloxycarbene. The parent cationic bridging formate complex [(TiX3)2(μ2‐OCHO‐κO:κO′)][B(C6F5)4], 4[B(C6F5)4], was simply deprotonated with the strong base K(N(SiMe3)2) to give 5. Complex 5 reacts smoothly with CO2 to generate the bridging oxalate complex [(TiX3)2(μ2‐C2O4‐κO:κO′′)], 6, in a CC bond formation reaction commonly anticipated for oxalate formation by reductive coupling of CO2 on low‐valent transition‐metal complexes.